Vocabulary of The Extinct Tugu Portuguese Creole Dialect Used by The Portuguese Descendants In Tugu Village, North Jakarta - Taufiqurrahman, Febri (Universitas PGRI Palembang, 2023)
At that time, the Tugu Portuguese Creole dialect was used as the primary means of communication to purposely prevent members of the VOC from understanding them (Suratminto, 2010). Eventually, due to such isolation, the Tugu Portuguese Creole dialect had become extinct, with only a small percentage of vocabulary and clauses retained in cultural references. A qualitative method is applied to determine how the Portuguese descendants use the vocabulary from the Tugu Portuguese Creole dialect to reinforce their cultural identity. This research finding that the cultural identity of the Portuguese descendants was reinforced through various means. First, some of the Tugu Portuguese Creole vocabulary has been preserved in the Keroncong Tugu songs, which are still being performed and passed down to subsequent generations. Moreover, music groups of Portuguese descent have performed these songs at various events, while wearing traditional clothes. Second, the names from the Tugu Portuguese Creole dialect are still being used for kinship system of Tugu Portuguese Descendants and certain instruments of keroncong. The implication of the findings is that such actions can be used by other cultures to strengthen their cultural identities, regardless of whether the dialect is currently being used as the primary means of communication.